Effectiveness of the Consecutive Alternating Administration Course of a Triple Antiviral Combination in Coxsackievirus B3 Infections in Mice - Vassileva-Pencheva, R.; Galabov, A. S. (Drug Research, 2016)
Anti-enteroviral chemotherapeutics for clinical use are not registered so far, mainly due to the rapid development of drug-resistance. One of the possible approaches to overcome this problem is the use of combined chemotherapy. However, its application consisting of simultaneously given drugs, is not efficacious because of the development of multiple resistance. Here we present a novel approach for combined application of anti-enteroviral compounds, consisting of a consecutive alternating administration (CAA) course. CAA was tested on 2 in vivo models of Coxsackievirus B3 infection in newborn mice at inoculation dose of 20 MLD50 (50% mouse lethal dose): neurotropic (Nancy strain) and cardiotropic (Woodruff strain) infections. Compounds partnering in a triple combination were selected as enterovirus (EV) replication inhibitors with different mode of action – disoxaril (a VP1 blocker), guanidine.HCl (targeting 2C protein) and oxoglaucine (attacking 3A coding region). The application of this combination by CAA course resulted in around 40 and 60% survival rate in mice infected with Nancy and Woodruff virus, respectively, accompanied by a marked lengthening of the mean survival time (MST). The results obtained are proofs for the prospect of the treatment course by a triple combination through the CAA scheme as an approach interfering the occurrence of drug resistance at EV infections.
Keywords: antiviral drugs; drug research; infectious diseases